German Writers and the Politics of Culture - Cooke, Paul. author. aut Link
XXI, 262 p.
Keywords: Before the fall of the Berlin Wall many East German writers were praised in the Western world as dissident voices of truth, bravely struggling with the draconian constraints of living under the GDR's communist regime. However, since unification, Germany has been rocked by scandals showing the level to which the Stasi, the East German Secret Police, controlled these same writers. This is the first study in English to systematically explore how the writers have responded to the challenge of dealing with the Stasi from the 1950s to the present day.